Pelaksanaan Manajemen Kelas dalam Meningkatkan Minat Belajar Siswa di MA Daarul Qur’an Klari Kabupaten Karawang - Anisah Lamis; Ahamad Junaedi Sitika; Debibik Nabila Fauziah (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Class management is the activities a teacher seeks to create a class situation conducive to achieving the ultimate learning goals. Ma Daarul Qura'an Klari Karawang is an islamic education organization with one of the vision associated with class management in increasing interest in learning that is the resilient and professional management management governance of madrassa. It discusses the class management that teachers do in order to increase the student's interest in learning in ma darul qur 'an klari. The methods used in this study are descriptive qualitative with observation, documentation and interview data sources. Research shows that teachers have 3 classes of class management which are division of the group, the presentation of duties, and the personal approach teachers make to students, all three are influential enough to develop student learning interests in ma daarul the qur 'an klari. As for the inhibitors to perform class management in increasing the interest in students' learning in ma darul the qur 'an klari, which is student indiscipline, in which some students do not have a student's worksheet (LKS) and thus causing students to be late for the task force. The cooperation and coordination between teachers and the support of the school administration should be carried out well.